Thermal Transient and Thermal Stress on Radiated Heat Float Glass - Eko Julianto; Waluyo Adi Siswanto; Pebli Hardi (JSE Journal of Science and Engineering, 2020)
To conduct an experiment of thermal radiation. The researchers conducted a simulation to study the behavior of the damage float glass using Mecway 10 FEA software. The ambient time and temperature on the first float glass sheet sustaining thermal transient and thermal stress are the most important parameters to find out the part of float glass. Analyzing the results of all simulations of radiant heat and convection in transient thermal simulations on the surface of float glass to be crack and knowing the estimated time until cracked float glass with thermal stress analysis. Giving heat radiation to the exposed glass surface, to be assumed by heat exposure from 0 to 20 minutes which is 32º to 600ºC with 19 mm glass thickness using Mecway 10 FEA software. Then did a comparison of the radiation heat value convection flow rate and so that the glass experiences a thermal crack. In this process, the results of the comparison will also be reviewed and discussed at the limit of the amount of heat radiation so that the cracked glass or thermal crack. The difference in temperature and stress will increase with adding radiation heat on the glass. Critical time and temperature differences are given as reference values ​​to predict Thermal stress in computerized applications.